APPLYING DLTA STRATEGY ON TEACHING LISTENING COMPREHENSION - Budiyanto, Darmawan; Aprillitzavivayarti, Aprillitzavivayarti; Ridho, M. Rasyid (Jurnal Ilmiah Bina Edukasi, 2021)
The objective of this study is to find out whether it is effective or not to teach listening comprehension by using DLTA strategy. Population of this study was the seventh grade students of SMPN 46 Palembang in academic year 2020/2021 with the sample were taken from class VII. 1 consists of 34 students by using cluster random sampling. Method of this study was the pre Â experimental with pre-test and post-test. The data were obtained by using test in 20 multiple choices. SPSS 17 was used to analyze data and the paired t Â test was applied. Based on analysis data, the writer found that the mean score in pre-test was 58.38 and in post-test were 72.06. The result of value of t-obtained was 22.476, this score was higher than 2.0345 as its critical value. It means that the null hypothesis (Ha) was rejected and alternative hypothesis (H0) was accepted